2019
DOI: 10.1177/1474904119893916
|View full text |Cite
|
Sign up to set email alerts
|

Relational analysis of the phenomenon of early school leaving: A habitus typology

Abstract: Although there is an extensive body of literature on the causes and consequences of early school leaving (ESL), little is known of how early school leavers cope with their situation after having left the education system. This paper’s main objective is to fill this research gap. At first we look at developments in the social positioning of early school leavers in Austria that show that their situation has deteriorated not only because of changes in the labour market (e.g. due to globalization) but also because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This typology was based on three school axes: behavioral maladjustment, commitment, and (academic) achievement. Later studies (Bowers et al, 2012;Fortin et al, 2006) broadened this view and sought an explanation for ESL in the combination of factors related to young people's learning experiences, emotional and mental well-being, behavior and, in some cases, family background (McDermott et al, 2017(McDermott et al, , 2018Nairz-Wirth & Gitschthaler, 2020;Ogresta et al, 2021). They showed that not all students who drop out of school had low academic performances.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This typology was based on three school axes: behavioral maladjustment, commitment, and (academic) achievement. Later studies (Bowers et al, 2012;Fortin et al, 2006) broadened this view and sought an explanation for ESL in the combination of factors related to young people's learning experiences, emotional and mental well-being, behavior and, in some cases, family background (McDermott et al, 2017(McDermott et al, , 2018Nairz-Wirth & Gitschthaler, 2020;Ogresta et al, 2021). They showed that not all students who drop out of school had low academic performances.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…To achieve this, researchers use one of the types of qualitative interviews. The first two of the three analyzed qualitative studies tried to address the research issues regardless of respondent ethnicity and background (Nairz-Wirth & Gitschthaler, 2020;Ogresta et al, 2021), in the most recent of the analyzed studies, the researchers focused on a specific group of Finnish residents, predominantly Romany prisoners (Pikkarainen et al, 2021). (3) To test the predictive validity of the typology.…”
Section: Research Methods and Research Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Relevant literature uses the terms dropout and early school leaving (ESL) for this phenomenon (Lamb, Markussen, Teese et al, 2011;Nairz-Wirth, Gitschthaler, 2019;OECD, 2012). As both terms (dropout, early school leaving) can be considered equivalent, they will be used as synonyms in this paper.…”
Section: Theoretical Definitionmentioning
confidence: 99%
“…xperiences of successful learning and positive interpersonal relationships are important for school engagement (Quin, 2017;Upadyaya & Salmela-Aro, 2013). However, this is not everyone's experience of school and attempts to understand the reasons for early school leaving show that many experience the opposite (Cederberg & Hartsmar, 2013;Nairz-Wirth & Gitschthaler, 2019;Tuck, 2011). Learning about the subjective perspectives of people slipping out of schooling can widen our understanding of the processes behind early school leaving.…”
mentioning
confidence: 99%